Kerjasama Guru Bimbingan Konseling dan Guru Pendidikan Agama Islam Dalam Membentuk Karakteristik Religius Siswa SMP 1 Sungai Pinyuh Setelah Bulan Ramadhan - Hiqqal, Muhammad (BKI IAIN Pontianak, 2023)
Abstract: Awareness of worship is very important in the process of forming religious characteristics for students. Religious characteristics need to be instilled early with continuous direction and supervision from parents and teachers, this can develop the potential of students so that they are able to reach the stage of maturity and realize the importance of worship in life. Thus, there needs to be cooperation between counseling guidance teachers and Islamic religious education teachers to raise awareness of worship to students, especially after the month of Ramadan is over. This study aims to teach adolescents of SMP 1 Sungai Pinyuh that the month of Ramadan is a very good opportunity to increase awareness in worship. This research also seeks to find out whether adolescents of SMP 1 Sungai Pinyuh still commit social crimes after the holy month of Ramadan. This research uses descriptive qualitative methods with the type of field research. The subjects in this study were Islamic religious education teachers and counseling guidance teachers. The techniques used in data collection in this study are interviews, observation, and documentation. Then the analysis used in this research is data reduction, data presentation, and conclusion drawing. The result of this study is that the month of Ramadan does not make a benchmark for students of SMP 1 Sungai Pinyuh to stop committing acts of social pathology. There needs to be guidance from educators so that students are more aware of their nature as creatures of Allah. The form of cooperation carried out by the counseling teacher and PAI teacher is by making activities in the form of Al-Qur'an tadarus, religious guidance, Friday blessings and making PAI teachers and counseling teachers as role models while at school.